Survey sampling theory and methods - Chaudhuri Arijit; Stenger Horst (Boca Raton Chapman & Hall, 2005)
This new edition of Survey Sampling: Theory and Methods has been updated to include the latest research and the newest methods. The authors have undertaken the daunting task of surveying the sampling literature of the past few decades to provide an outst
Keywords: Sampling(Statistics)